2019
DOI: 10.1111/ggi.13690
|View full text |Cite
|
Sign up to set email alerts
|

Functional training in postmenopause: Cardiac autonomic modulation and cardiorespiratory parameters, a randomized trial

Abstract: Aim To evaluate the influence of functional training on cardiorespiratory parameters and cardiac autonomic modulation in postmenopausal women. Methods A total of 39 apparently healthy postmenopausal women were randomized into two groups and analyzed: the group that carried out the functional training (FTG; n = 19; age 60 ± 4.5 years; weight 67.64 ± 11.64 kg) for 18 weeks, and the control group (CG) who did not undergo the training (n = 20; age 58.45 ± 4.8 years; weight 66.91 ± 13.24 kg). Blood pressure, heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Jones et al 14 analyzed the intensity of menopausal symptoms and HRV and reported a decrease in all HRV indices in both groups of postmenopausal women. Studies with different objectives also reported decreased cardiac autonomic regulation in postmenopausal women 7,9,[16][17][18] .…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Jones et al 14 analyzed the intensity of menopausal symptoms and HRV and reported a decrease in all HRV indices in both groups of postmenopausal women. Studies with different objectives also reported decreased cardiac autonomic regulation in postmenopausal women 7,9,[16][17][18] .…”
Section: Discussionmentioning
confidence: 94%
“…HRV allows the quantitative evaluation of autonomic balance and describes interval fluctuations between consecutive RR intervals 4,11 , which can be an additional resource in the evaluation of menopausal women [16][17][18] diagnosed with DES. Menopausal women are more likely to develop this condition, probably due to decreased androgens and estrogen production resulting in Meibomian gland dysfunction, and age-related factors 2,6,9,10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations